The Role of Meta-Cognitive Self Regulated Learning Strategies in Enhancing Language Performance: A Theoretical and Empirical Review - Mahadi, Rozilawati; Subramaniam, Ganakumaran (Journal of Asian Scientific Research, 2013)
Recent research suggests a potential link between meta-cognitive awareness,self regulated learning strategies and language performances. Self-regulated learning has garnered a great deal of interest among academicians and psychologists as research indicated that it has positive effects on learners' academic achievement (Dolianac, 1994; Dckeyrel et al., 2000) whereas experts advocate that “meta-cognitive awareness” ignites one’s thinking and can lead to a deeper learning and improved performance, especially among learners who are having problems in learning. Implicatively, this paper highlights the role of meta-cognitive self regulated learning strategies in enhancing performance among students by providing theoretical and empirical foundations drawn from literature on these aspects, specifically towards language achievements.